Topical Use Of Corticosteroids In Dermatology - Motghare Vijay; Thawani Vijay; Parate S M (Wolters Kluwer Medknow Publications, 1995)
Topical corticosteroids still constitute one of the largest groups of drugs being used in dermatology. Prescribing of this group of drugs was studied in dermatology out â€"patient department of Govt. Medical College Hospital, Nagpur by randomly auditing the prescriptions in the Hospital Pharmacy. Out of 600 prescriptions monitored, 14 could not be deciphered, 136 contained prescriptions for topical steroids, 37 had in addition systemic preparations and the 47 were only prescribed systemic drugs. Data with regard to age and sex and the diagnosis were noted. The prescriptions were scrutinized for mentioning of dosage form, quantity, frequently, site of application and duration of topical steroids. The importance of these parameters has been discussed along with the report of the findings of the study. The topical steroids prescribed have been discussed along with the report of the findings of the study. The topical steroids prescribed have been classified according to potency.